2020
DOI: 10.1080/14616696.2020.1831038
|View full text |Cite
|
Sign up to set email alerts
|

The impact of distance learning on the social practices of schoolchildren during the COVID-19 pandemic: reconstructing values of migrant children in Poland

Abstract: In response to the COVID-19 pandemic, the Polish government decided to shut down all public and private institutions, including schools, from 12 March 2020. Since then, 4.58 million students from 24,000 schools have remained in their homes and practiced distance learning. Distance learning has greatly affected children's social practices, including domestic, everyday, specialist, and cultural practices. This paper applies social practice theory, rooted in Schatzki's ontological theory of practices, and Shove, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 20 publications
0
45
0
5
Order By: Relevance
“…Learning during the pandemic became a particular challenge for migrant children. Adjustment to new daily routines and changing learning habits triggered a complex process of redefinition of social practices by migrant children living in Poland (Popyk 2020). In many situations, schoolchildren reported that homework and remote learning was more tedious.…”
Section: Educational Inequalitiesmentioning
confidence: 99%
“…Learning during the pandemic became a particular challenge for migrant children. Adjustment to new daily routines and changing learning habits triggered a complex process of redefinition of social practices by migrant children living in Poland (Popyk 2020). In many situations, schoolchildren reported that homework and remote learning was more tedious.…”
Section: Educational Inequalitiesmentioning
confidence: 99%
“…The questionnaire was referring to these issues and developed on the basis of studies on migrant workers' opinions regarding crisis situations and changes in living conditions in the host country [1] , [2] , [3] , [4] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Pembelajaran daring dan lingkungan belajar yang menarik memiliki peran yang signifikan dalam pengembangan akademik dan prestasi siswa dalam pembelajaran (Ibem, Alagbe, & Owoseni, 2017). Selain itu pengelolaan pembelajaran dan pengelolaan kelas yang tepat akan berdampak pada proses sosial dan menumbuhkan suasana belajar yang menggairahkan (Cahyanto, Akbar, & Sa, 2018;Popyk, 2021).…”
Section: A Pendahuluanunclassified